Sex ratio of infectious mononucleosis and possible relevance to multiple sclerosis. - Ramagopalan, S; Giovannoni, G; Yeates, D; Seagroatt, V; Goldacre, M (2013)
Infectious mononucleosis (IM) is associated with the risk of developing multiple sclerosis (MS). Using databases of hospital admissions for England (1999-2005), we investigated the female-to-male ratios (FMRs) for admission to hospital for IM and MS stratified by age. Males were more frequently admitted for IM for all age groups apart from ages 10-14 (FMR 1.50; 95% confidence interval (CI) 1.36-1.64) and, borderline significantly, at ages 15-19 (FMR 1.03, 95% CI 0.99-1.08). This intriguing aspect of IM epidemiology in adolescence, the atypical female excess, may be linked to the sex ratio of MS, where females predominate from adolescence.